2022
DOI: 10.1007/s10874-022-09440-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporary reduction in VOCs associated with health risk during and after COVID-19 in Maharashtra, India

Abstract: A novel coronavirus has affected almost all countries and impacted the economy, environment, and social life. The short-term impact on the environment and human health needs attention to correlate the Volatile organic compounds (VOCs) and health assessment for pre-, during, and post lockdowns. Therefore, the current study demonstrates VOC changes and their effect on air quality during the lockdown. The findings of result, the levels of the mean for total VOC concentrations were found to be 15.45 ± 21.07, 2.48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 114 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…A study conducted in Delhi reported that anthropogenic VOC contribution varied between 60–70% in traffic intersection sites ( Kashyap et al, 2019 ). A similar study claimed that workplace cancer risks were reported highest at traffic intersections, followed by industrial sites ( Kumar et al, 2020 ; Singh et al, 2022b ). Although various studies have been reported for early phases of lockdown in countries such as China, Italy, USA ( Dutheil, Baker & Navel, 2020 ; Tobías et al, 2020 ; Xu et al, 2020 ); and a few studies on metropolitan cities of India such as Delhi and Mumbai ( Jain & Sharma, 2020 ; Mahato, Pal & Ghosh, 2020 ; Sharma et al, 2020 ; Sahoo et al, 2020 ; Singh et al, 2021c ); however, a detailed analysis involving various phases of lockdown and unlockdown is essential.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…A study conducted in Delhi reported that anthropogenic VOC contribution varied between 60–70% in traffic intersection sites ( Kashyap et al, 2019 ). A similar study claimed that workplace cancer risks were reported highest at traffic intersections, followed by industrial sites ( Kumar et al, 2020 ; Singh et al, 2022b ). Although various studies have been reported for early phases of lockdown in countries such as China, Italy, USA ( Dutheil, Baker & Navel, 2020 ; Tobías et al, 2020 ; Xu et al, 2020 ); and a few studies on metropolitan cities of India such as Delhi and Mumbai ( Jain & Sharma, 2020 ; Mahato, Pal & Ghosh, 2020 ; Sharma et al, 2020 ; Sahoo et al, 2020 ; Singh et al, 2021c ); however, a detailed analysis involving various phases of lockdown and unlockdown is essential.…”
Section: Introductionmentioning
confidence: 83%
“…In the present study, secondary data on gaseous pollutants such as nitrogen dioxide (NO 2 ), Nitrogen oxide (NO), oxide of Nitrogen (NOx), sulfur dioxide (SO 2 ), ammonia (NH 3 ), and ozone (O 3 ) were collected from the Central Pollution Control Board (CPCB) on a daily basis. To determine the relative changes (%) in gaseous pollutants for pre-, lockdown, and unlockdown stages, data from January 1, 2020, to September 30, 2020, was collected from CPCB ( https://app.cpcbccr.com/ccr/#/caaqm-dashboard-all/caaqm-landing ) as previously described in Singh et al (2022) ; Singh et al (2022a) ; Singh et al (2022b) .…”
Section: Methodsmentioning
confidence: 99%
“…In the last few decades, urban air pollution has become a serious environmental problem, especially in developing countries, including India (1)(2)(3)(4). Widespread industrialization, rapid urban planning, and a large increase in the number of vehicles with a high population density have been responsible for a deterioration in the ambient air quality (5)(6)(7)(8). Among air pollutants, polycyclic aromatic hydrocarbons (PAHs) are among the most important due to their impact on both health and climate (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to shallower boundary layer depths, higher concentrations of aromatic volatile organic compounds (VOCs) and CO were found in the wintertime and transported from the polluted Indo-Gangetic Plain region. Relatively high loadings of benzene (~30%), toluene (45%), and CO (32%), respectively, were observed in vehicle exhaust by using the positive matrix factorization analysis method [ 34 ].…”
Section: Introductionmentioning
confidence: 99%